Investigation of inconsistency between active and non-active US-industry security quote - Jiang, Xiao Zhong (2008)
The US treasury bills, notes, and bonds are auctioned regularly. The newly auctioned treasury securities are actively traded, their prices being used as benchmarks. These securities gradually become less active, as new securities are auctioned. Thus majorities of treasury securities are not actively traded, and their listed prices are indicative only, may or may not reflect their market value. In this project we investigate the price discrepancies between active and non-active treasury bonds, making use of a newly developed interest rate term structure. The result indicates that off-the-run bonds and on-the-run bonds may have different dynamics. Therefore market factors have to be considered when pricing off-the-run bonds, apart from the arbitrage-free condition.